Histopathologic patterns of nonrejection injury in renal allograft biopsies and their clinical characteristics; a single centre south Indian study - Clement Wilfred Devadass; Vijaya Mysorekar; Greeshma Prasad; Sravanthi Sunkaraneni; Gireesh Mathihally; Mahesh Eshwarappa; Radhika Kunavil (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Graft dysfunction (GD) is the major complication of renal transplantation, and may result in graft loss. The major causes of GD are immunological rejection and non-rejection injury (NRI), which have different prognostic and therapeutic connotations. Meticulous renal allograft biopsy (RAB) evaluation and its correlation with clinico-laboratory features are crucial for timely identification of the varied NRI. Objectives: To evaluate the clinico-laboratory characteristics and histopathologic features of NRI in "clinically indicated" RABs in our institution. Patients and Methods: This was a prospective study conducted over a period of five years on renal transplant recipients who underwent "clinically indicated" RAB for GD. Results: A total of 192 biopsies were evaluated which showed NRI, rejection and NRI with concurrent rejection in 57.3%, 26.6% and 3.6% cases respectively. The NRI category, with or without concurrent rejection, comprised of acute tubular injury (ATI) (44%), calcineurin inhibitor induced (CNI) toxicity (19.7%), infections (12.8%), recurrent glomerulonephritis (GN) (7.7%), de novo GN (1.7%), chronic interstitial nephritis (9.4%), thrombotic microangiopathy (2.6%) and renal vein thrombosis (1.7%). Mean patient age was 34.9 years with male: female ratio of 8:1. Conclusion: Timely differentiation between rejection and NRI is indispensable for improved allograft survival. Acute tubular injury is the major NRI causing delayed graft function (DGF), and is commonly associated with deceased donor renal transplantation. The blood concentration of CNI does not correlate with the extent of renal damage. Acute tubular injury and CNI toxicity are the major NRI, in the first six months post-transplantation and after six months post-transplantation, respectively.